2009
DOI: 10.1266/ggs.84.191
|View full text |Cite
|
Sign up to set email alerts
|

Induction of extracytoplasmic function sigma factors in Bacillus subtilis cells with membranes of reduced phosphatidylglycerol content

Abstract: The Bacillus subtilis gene pgsA, which codes for the phosphatidylglycerophosphate synthase that catalyzes the committed step for the synthesis of phosphatidylglycerol (PG), is essential since Pspac-pgsA cells require IPTG for growth. Removal of the inducer caused a dramatic decrease of PG content in the membranes of cells and retarded growth. At 60 min and 120 min after removal, it was reduced to 14.1% and 8.9% of total lipid, respectively, from an initial content of 28.1%. We conjectured that the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…yku (encoding a hypothetical thiol:disulfide oxidoreductase) and sigV contain SNPs, therefore it is uncertain how the functions of these proteins are affected. Nevertheless, the sigV mutation is interesting because sigV is expressed upon cell wall stress (Hashimoto et al, 2009;Hashimoto et al, 2013), perhaps induced by malfunctioning TagE. Although it has been suggested that ECF sigma factor s V is functionally redundant because of regulon overlap (Mascher et al, 2007), mutations tuning s V affinity may still be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…yku (encoding a hypothetical thiol:disulfide oxidoreductase) and sigV contain SNPs, therefore it is uncertain how the functions of these proteins are affected. Nevertheless, the sigV mutation is interesting because sigV is expressed upon cell wall stress (Hashimoto et al, 2009;Hashimoto et al, 2013), perhaps induced by malfunctioning TagE. Although it has been suggested that ECF sigma factor s V is functionally redundant because of regulon overlap (Mascher et al, 2007), mutations tuning s V affinity may still be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining mutated genes are bmrU, yhaU and sigV. bmrU is part of an operon-encoding multidrug transporter Bmr and regulator BmrR and is expressed, for example, under glucose starvation (Petersohn et al, 1999;Petersohn et al, 2001), yhaU encodes a K þ /H þ antiporter for K þ efflux (Fujisawa et al, 2007) and sigV encodes one of seven extracytoplasmic function (ECF) sigma factors and is related to cell envelope homeostasis and antibiotic resistance (Mascher et al, 2007;Hashimoto et al, 2009Hashimoto et al, , 2013Matsuoka et al, 2011).…”
Section: Whole-genome Sequencingmentioning
confidence: 99%
“…The sigma factor can be released from its inhibitor upon receiving a stimulus from the environment, thereby coupling cytoplasmic transcriptional response to extracellular signals. In E coli, acute drop in membrane PG content (by removing a synthetic inducer of a pgsA artificial construct) rapidly induced transcriptional activity of sigma M, which is normally known to mediate responses to high salt exposure (45). This might suggest that detection of changes in membrane PG linked to membrane permeability can be an important component in stress response.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…31,32) It is suggested that the lipid composition of the membranes is associated with the activity of anti-ECF sigma protein. Judging by the gene annotation of O. iheyensis, its genome lacks pssA and psd (genes for phosphatidylethanolamine synthesis), mprF (a gene for lysylphosphatidylglycerol synthesis), and ugtP (a gene for glycolipids synthesis).…”
Section: Discussionmentioning
confidence: 99%